Paranoid Thinking and Wellbeing. The Role of Doubt in Pharmacological and Metacognitive Therapies - Asensio-Aguerri, Leonor; Beato-Fernández, Luis; Stavraki, Maria; Rodríguez-Cano, Teresa; Bajo, Miriam; Díaz, Darío (Frontiers in Psychology, 2019)
Introduction. Pathological confidence in one’s thoughts is a key mechanism of chronic paranoid thinking. For this reason, many of the current therapies focus on trying to reduce it. In fact, the way some antipsychotics (e.g., haloperidol) work seems to be through the induction of doubt. Because of the impact of these pathological thoughts on positive health, studying the well-being of people who experience paranoid thoughts is fundamental. The first objective of this research is to apply the Complete State Model of Health (CSMH) to a sample of patients characterized by the presence of paranoid thinking. Our second objective is to evaluate the impact of therapies based on reducing pathological confidence on patients’ well-being. Methods. Sixty participants with SCID-5 confirmed DSM-5 diagnosis related with paranoid thinking and without mood symptoms were recruited. In order to test the existence of a two continua model of mental health (CSMH), we conducted a parallel analysis and an exploratory factor analysis. To test our hypothesis regarding the partially mediating role of doubt between paranoid thinking and patients’ well-being, we conducted a biased corrected bootstrapping procedure. Results. As expected, two different unipolar dimensions emerged from the measures used to assess paranoid thinking and positive health (two continua model of mental health). When patients received metacognitive and pharmacological treatment, more paranoid thinking led to more doubt in all thoughts, which in turn affected well-being. The analyses carried out confirmed the partial mediating role of doubt. Conclusions. Despite the efficacy shown by both metacognitive therapies and antipsychotics, it seems that they not only reduce pathological confidence, but can also affect other thoughts not linked to delirium. This effect of generalization of doubt in all thoughts negatively affected patients’ well-being and quality of life.